Rooted and radiant : women's narratives of leadership - Teig, Trisha; Devies, Brittany; Shetty, Rebecca (Contemporary perspectives on leadership learning., 2023)
"Rooted and Radiant: Women's Narratives of Leadership shares the narratives of 39 women navigating the process of leadership. It seeks to honor the unique experiences of the authors while also challenging the dominant stories of the leadership process. The audience for the book is leadership educators and women looking to further explore leadership as a phenomenon. Rooted and Radiant: Women's Narratives of Leadership is grounded in the hope and radiance described by Skye, one of the many voices in this collection. The book is filled with narratives from women exploring their own stories of leadership and gender. These stories are woven together by an author team committed to centering the voice and lived experiences of these narrative authors. This book begins with important literature framing around women and leadership. The early chapters also explore the research process of this book in-depth. The core of the book includes chapters focused on critical themes found in the 39 narratives and weaving together women's narratives of understanding and enacting leadership. The book concludes with critical hope about women and leadership moving forward"--